Spatial familiness and family spatialities—searching for fertile ground between family business and regional studies - Rodrigo Basco; Lech Suwala (Family Business and Regional Development, 2021)
This chapter searches for common fertile ground between the disciplines of family business studies and regional studies. Most existing studies linking both disciplines are fragmented and dispersed, thereby obstructing a systematic assessment of the cross fertilisation of knowledge. Based on their relationships to different spatial entities—a superordinate term for spatial factors, spatial structures, spatial processes, spatial contexts, spatial scales, spatial settings, spatial policies, and spatial concepts—we take stock of recent studies and attempt to shed new light upon the nexus of both disciplines. We present two more advanced theoretical models (i.e., the spatial family management model and the regional familiness model) that already incorporate the notion of spatial entities. We use these conceptual models to reflect on future lines of research and call for more interdisciplinary work to address research gaps and exchange insights around the ideas of `spatial familiness' and `family spatialities' on theoretical, empirical, and practical grounds.
Keywords: R2; R50; R11; R12; R58; 330; Family Firms; Regional Development; Regional Economics; Economic Geography; Regional Studies; Regional Science